MAQASID SYARIAH SEBAGAI DASAR PARADIGMA EKONOMI ISLAM - M. Iqbal (Sekolah Tinggi Agama Islam Sumatera Medan, 2019)
Maqāṣid ash-Shari'ah in language has the meaning ‘purpose of Shari'ah. Defines the maqasid of shari'ah with the meanings and objectives maintained by syara 'in all its laws or most of its laws, or the ultimate goal of the Shari'ah and the secrets laid by syara 'to every law. Maqāṣid syari'ah aims to guarantee the benefit of mankind in the world and the hereafter, including fulfilling the benefit of economic interests as well as the application of economics in sharia principles. Maqasid Syariah which is fundamental in the economic paradigm of Islam is: guarding religion, keeping lives, guarding offspring, maintaining property rights, and guarding reason.